Measuring Permanent Exits from Homeless Emergency Shelters in Toronto - Dutton, Daniel J.; Kneebone, Ronald D. (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
The use of homeless shelters is dynamic. On any given day, some of those occupying a shelter bed are staying in shelter for the first time, others are returning to shelter after time away, and still others are staying in shelter for the last time. Deriving a method for measuring the number of people leaving the shelter system for the last time is an essential step in understanding the reasons for those exits. Any approach for identifying permanent exits from a shelter system must face the challenge of right censoring, the fact that observations of permanent exits may occur after the end of one’s data set. This paper describes an approach for addressing the problem of right censoring and uses it to measure permanent exits from Toronto homeless shelters.